Outcomes of Complete Repair of Mixed-Type Total Anomalous Pulmonary Venous Return - Mohannad Dawary; Fareed Khouqeer; Ziad Issa; Louai Alkhalaf; Faisal Alshamdin; Massimo Griselli (Kardiyovasküler Tıp E Dergisi/E Journal of Cardiovascular Medicine)
Objectives: To retrospectively review 14 cases, describe preoperative imaging, anatomic findings and confirmation at surgery, surgical technique, and outcomes. Materials and Methods: We describe anatomic variations in mixed-type total anomalous pulmonary venous return and surgical outcomes in a case series from 2 centers. Mixed-type total anomalous pulmonary venous return is classified based on the pattern of pulmonary venous drainage. Type I refers to ‘2+2’ drainage of venous pairs, type II refers to ‘3+1’ and type III refers to all other variants. Six patients (43%) had type I “2+2” drainage; 2 patients had 2 supra-cardiac and 2 cardiac connections, and 4 patients had 2 infra-cardiac connections and 2 cardiac. 4 patients (29%) had type II “3+1” drainage. Three patients had 3 cardiac and 1 supra-cardiac variants and one had a rare supra-cardiac pulmonary venous combination. 4 patients (29%) had type III morphology. 2 patients of them had 3+2 anatomy with 3 supra-cardiac and 2 cardiac connections, both of which included 3 right-sided pulmonary veins. The remaining 2 patients had unique anatomy, one with tri-level attachment to cardiac, supra-cardiac, and infra-cardiac and the last with all supracardiac pulmonary venous drainage but in a “3+1+1” pattern. Results: In previous publications, mixed-type total anomalous pulmonary venous return has a higher mortality rate, with univariate analysis of mixed-type versus cardiac type with statistically significant hazard ratios of 2.88 in previous study and mortality as high as 42-50%. We achieved improved outcomes, with overall survival of 79% and no intraoperative mortality. Both patients who had complex intracardiac lesions (1 with ventricular septal defect and 1 with tetralogy of fallot) ultimately died. Of the remaining patients, 29% developed pulmonary venous obstruction on echocardiography follow-up with 3 requiring interventions with cardiac catheterization. Conclusion: Mixed-type total anomalous pulmonary venous return has a wide variety of connections, which contributes to the complexity of planning and surgical correction. Further studies are needed to better understand the different morphologies of the disease.